Development of a new pylon material in transtibial prosthesis / Hanie Nadia Shasmin - Hanie Nadia , Shasmin (2012)

(untitled)
Introduction: Amputations among Malaysia citizens is increasing at an alarming rate. This people are in need of lower leg prostheses but are unable to afford the high costs of current prosthetic components. In this study, bamboo was used to replace the conventional pylon material to reduce the cost in below knee prosthesis. Bamboo is a natural fiber-reinforced composite material possesses good mechanical properties to warrant its use as a structural material. Methodology: The bamboo pylon was produced from proper harvesting of Bambusa Heterostachya. It was then dried in an oven at 200o Celsius for 72 hours. Before lamination, the bamboo culm underwent pre-treatment with V-Sawit oil at about 120°C for about 30 to 90 minutes. Bamboo pylon was laminated with at least 3 layers, using vinyl urethane adhesive and polyvinyl acetate. The processes involved in producing bamboo pylon ensure its durability and protection against pest. In second part of the study, bamboo pylon was tested for flexural, compressive and tensile properties under Universal Testing Machine based on ASTM standards. In addition, computer simulation of subject walking with bamboo pylon was performed. The third part of the study involved gait comparisons on six transtibial amputees while walking with bamboo and stainless steel pylon with the prosthetic legs. Results and Discussions: The results showed with yield compressive stress and Young’s modulus of 132.6 MPa (SD ± 3.3 MPa) and 30.7 GPa (SD ± 4.7 GPa) respectively, bamboo pylon was three times stronger than fibre reinforced plastic and two times stronger than Aluminum. There was no significant difference found in vertical and antero-posterior ground reaction forces (p > 0.05) in Bamboo prosthetic leg compared to Stainless steel prosthetic leg. Joint kinematics for Bamboo prosthetic leg was also comparable to joint kinematics for Stainless steel prosthetic leg (p > 0.05) except for the hip extension (p < 0.05). In spatio-temporal parameters; cadence, step length and walking speed of Bamboo prosthetic leg were comparable to Stainless steel prosthetic leg (p > 0.05). Conclusions: Bamboo is a low-cost material and possesses great mechanical properties. It will make an excellent new pylon material in transtibial prosthesis.